The Impact of Coal Combustion Waste (Fly Ash and Bottom Ash) on The Properties of Clay Soil (Case Study: National Road Section Demak – Kudus, Indonesia) - Nurtaqwim, Alien Maulida; Soemitro, Ria Asih Aryani; Warnana, Dwa Desa; Satrya, Trihanyndio Rendy; Putra, Yanuar Dwi (Journal of Infrastructure & Facility Asset Management, 2024)
The National Road Section Demak - Kudus is one of the most populous road sections connecting East Java province with West Java province through the city of Semarang. Repeated damage conditions raise the suspicion that the subgrade under the road body has special criteria that need further handling before repairs are made to the pavement. In addition, based on the soft soil distribution map and soil data with the results of existing laboratory testing, categorized as soft soil. For this reason, it is necessary to handle the subgrade to improve soil parameters, which is physical and mechanical. Therefore, chemical stabilization was chosen to obtain a chemical reaction from the soil. The selected chemicals to induce these reactions is coal combustion waste which are fly ash and bottom ash. Exhibiting pozzolanic properties that can react and cause flocculation in the soil. The research involves mixing the soil with stabilizing materials in three different combinations: first, soil mixed by fly ash (FA); second, soil mixed by bottom ash (BA); and third, soil mixed by both fly ash with bottom ash (FABA), optimum stabilizing mixture material at 20%. The initial soil, which is highly plastic clay with a classification of CH/A-7-6, having a plasticity index (PI) of 43.23% and California Bearing Ratio (CBR) of 0.92%, undergoes improvement with adding FA stabilizer, resulting in MH/A-7-5 with a PI of 27.07% and CBR of 12.39%. The mixture of soil with FABA is MH/A-7-5 with a PI of 28.87% and CBR of 9.60%. However, the improvement in the mixture of soil with BA is not as significant, remaining in the CH/A-7-6 category with a PI of 31.83% and CBR of 3.00%.